Does integrating personal data via CDPs improve banking responsiveness? Moderating influence of local culture - Tabelessy, Walter; Ralahallo, Fransiska Natalia; Chaniago, Anggraini; Kurniawan, Sabda Aji; T, Glen Andre Yusuf (Asian Management and Business Review, 2026)
In the growing importance of personalized digital services in the banking sector, the integration of personal data through customer data platforms (CDPs) has become a strategic priority. This study explores how personal data privacy influences perceived personalization and operational efficiency in digital banking services, while also investigating the moderating role of local culture. The research is motivated by increasing consumer demands for both personalized services and greater control over personal data. Personal data privacy was conceptualized as a multidimensional construct comprising knowledge, experience, control, willingness to value privacy, and trust. A quantitative method using partial least squares structural equation modeling (PLS-SEM) with 10,000 bootstrapping resamples was employed. The analysis was conducted using SmartPLS version 4.1.1.4, which enables efficient estimation of complex models. Data were collected offline from 200 respondents who are active users of digital banking services from Himbara member banks. The results indicate that personal data privacy has a significant positive effect on both perceived personalization and operational efficiency. Among its dimensions, willingness to value privacy emerged as the most influential. Local culture was found to significantly moderate both relationships, suggesting that cultural context plays a critical role in shaping digital service outcomes. These findings contribute to theory and practice by highlighting the importance of integrating privacy protection and cultural sensitivity in the design of personalized digital banking services.